USAHA KEPALA SEKOLAH MENGIKUTSERTAKAN GURU DALAM PERENCANAAN PROGRAM SUPERVISI PENDIDIKAN UNTUK MENINGKATKAN PROSES KEGIATAN BELAJAR MENGAJAR PADA SEKOLAH DASAR NEGERI - Ina Marlina; Yudi Ekka Suryapriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this research is the school principal's efforts to involve teachers in planning educational supervision programs to improve pre-teaching and learning activities in public elementary schools in Subang district. The main problem in this research is how educational supervision programs in schools are implemented, in what cases teachers are included in planning educational supervision programs, how school principals involve teachers in educational supervision programs, and the difficulties faced by school principals in involving teachers in educational supervision program. The aim of this research is to describe the school principal's efforts to include teachers in planning educational supervision programs to improve the process of teaching and learning activities in public elementary schools in Subang district. The research method used was descriptive and a biographical study, by selecting 10 school principals out of 70 people as the population. From that population everything is used as the total sample. To collect data from school principals and teachers, a closed questionnaire was used, and the data processing technique used chi square with a significance level of 95% or 0.05. The results of the study showed that in carrying out supervision the principal always plans in advance, in preparing educational supervision programs the principal always includes teachers. in planning educational supervision by formally inviting, the difficulties faced by school principals involving teachers in planning educational supervision programs can be overcome.